A D-A-D' type organic molecule with persistent phosphorescence exhibiting dual-mode mechanochromism. (February 2020) - Huang, Lili; Liu, Jianwei; Liu, Lei; Yang, Qingyuan; Ma, Zhiyong; Jia, Xinru
Abstract: In this contribution, we report a new pure organic molecule ODBTCZ achieves fluorescence-RTP-DF triple emissions and dual-mode mechanochromism. ODBTCZ has an asymmetric D-A-D' structure with dibenzothiophene and carbazole as the donor and benzophenone as the acceptor. ODBTCZ shows remarkable solvatochromism in different organic solvent due to the intramolecular charge transfer (ICT) effect. Interestingly, crystals of ODBTCZ manifest multiple emissions of prompt fluorescence, delayed fluorescence and persistent phosphorescence at room temperature, which is quite rarely reported in pure organic molecules. The delayed fluorescence is not TADF verified by temperature-dependent experiments. The RTP has a long lifetime of 410 ms. Crystallographic analysis and TD-DFT calculation are conducted to elucidate the persistent phosphorescence. The enhanced intermolecular interactions highly constrain the motion of ODBTCZ in the crystal, impeding the quenching of oxygen and heat. A kind of dimer with enhanced parallel molecular packing acts more effectively to prompt ISC processes which further generates RTP and DF, due to the larger transition dipole moment and closer energy level between S1 and Tn . The unique triple-emission property endows ODBTCZ with dual-mode mechanochromism, namely fluorescence redshift and phosphorescence/DF on-off switch. This study is expected to contribute to develop stimuli-responsive luminescent switch with persistent RTP and lay the foundation for its wide applications. Graphical abstract: Image 1 Highlights: A D-A-D′ type organic molecule ODBTCZ was synthesized successfully. ODBTCZ showed persistent phosphorescence with the lifetime of over 400 ms. ODBTCZ exhibited dual-mode mechanochromism, namely fluorescence redshift and phosphorescence on-off switch.